Badingsanakan as social capital in character education: a qualitative analysis on banjar society - Ruswinarsih, Sigit; Budimansyah, Dasim; Wahyu, Wahyu; Sauri, Sofyan (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Publications on character education have become increasingly prevalent over the last ten years. However, there aren't many studies on the relationship between local wisdom, social capital, and character education. This article is sourced from research that explores the practice of badingsanakan, which is deeply embedded in the culture of the Banjar community. This paper aims to analyze the values in badingsanakan as a form of social capital that plays a role in character education. Using a qualitative approach to transcendental phenomenology, data was collected through in-depth interviews and participatory observations. The primary data source consisted of eight informants from various age, gender, and professional backgrounds. The results of the analysis revealed five main themes: empathy and solidarity, trust and openness, social responsibility, value learning, and strengthening social and cultural identity. These five elements are constructive social capital in the development of character education. The practice of badingsanakan reflects deeply rooted cultural values in social relations and serves as an authentic and contextually grounded approach to character formation. These findings recommend the integration of fraternal cultural values into character education strategies in both formal and non-formal settings to build a more meaningful and community-based education.